Ontology-based resources for bioinformatics analysis. (1st January 2011) - Viti, Federica; Merelli, Ivan; Calabria, Andrea; Cozzi, Paolo; Mosca, Ettore; Alfieri, Roberta; Milanesi, Luciano
A number of specific web accessible databases are developed in order to shed light into biomolecular data, providing novel perspectives about particular scientific problems or presenting innovative data integration approaches. Ontologies constitute an important enhancement, since they allow a better representation of biological data, by providing a hierarchical structure to organise information, enabling more effective queries, statistical analysis and semantic web searching. Here we present our experience in exploiting ontologies to enrich biomolecular databases in diverse biomolecular contexts. The semantic layer improves data organisation, accessibility and analysis and represents an invaluable support to identify relations among biological components.